2018
DOI: 10.1016/j.algal.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic and phenotypic diversity of the giant kelp, Macrocystis pyrifera, to support breeding programs

Abstract: The accelerated development of seaweed aquaculture is stimulating research on the genetic drivers of phenotypic diversity of the target species, in order to optimize breeding strategies, to help determine the choice of source populations, and for the selection of traits and varieties that fit with the environmental variability of the production site. This study investigates the spatial variation of the genetic and phenotypic diversities in natural populations of the giant kelp Macrocystis pyrifera, and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 72 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…The genetic structuring appears to be affected both by spread via ocean currents (Mooney et al, 2018) and by environmental variation and local adaptation (Nielsen et al, 2016). Similar studies of M. pyrifera populations along stretches of the American Pacific coast also identified several distinct genetic groups and suggested that both ocean currents and local adaptation to different environments can be important for this grouping (Alberto et al, 2011;Johansson et al, 2015;Camus et al, 2018).…”
Section: Invasiveness Introduction Of Non-native Genotypes and Gene mentioning
confidence: 66%
See 1 more Smart Citation
“…The genetic structuring appears to be affected both by spread via ocean currents (Mooney et al, 2018) and by environmental variation and local adaptation (Nielsen et al, 2016). Similar studies of M. pyrifera populations along stretches of the American Pacific coast also identified several distinct genetic groups and suggested that both ocean currents and local adaptation to different environments can be important for this grouping (Alberto et al, 2011;Johansson et al, 2015;Camus et al, 2018).…”
Section: Invasiveness Introduction Of Non-native Genotypes and Gene mentioning
confidence: 66%
“…Other peculiar modes of reproduction that can occur in Laminariales include apogamy, where a haploid sporophyte can emerge directly from a somatic cell of a gametophyte (Nakahara and Nakamura, 1973;Fang, 1984;Wu and Lin, 1987;Müller et al, 2019) (Figure 1C), and apospory, where a diploid gametophyte can develop from vegetative cells of a diploid sporophyte without any meiosis or spore formation (Nakahara and Nakamura, 1973;Lewis et al, 1993) (Figure 1D). Self-fertilization appears to be possible in most studied species of Laminariales (Wu and Lin, 1987;Brawley and Johnson, 1992;Kraan et al, 2000;Camus et al, 2018). Some kelp species are annual or biennial, but most are perennial (Schiel and Foster, 2006).…”
Section: Kelp Life Cyclesmentioning
confidence: 99%
“…Despite a fast-growing interest in commercial aquaculture, corresponding with a rapidly increasing global demand for nutrition supplementation and industry raw material, few researchers outside of Asia have explored sustainable domestication programs, including the creation of macroalgae germplasm banks [31,39,75,76]. Several facilities, such as the National Institute of Fisheries Science-Seaweed Research Center in South Korea and the Ocean University of China and Chinese Academy of Science, have dedicated infrastructure and research to the maintenance of commercially important macroalgal species and cultivars.…”
Section: International Cooperation and Collaboration Are Necessary Fomentioning
confidence: 99%
“…, Camus et al. ) as well as their historical phylogeographic diversification (e.g., Tellier et al. , Buonomo et al.…”
mentioning
confidence: 99%
“…In macroalgae, most genetic studies are focused on the population and regional levels and have mainly dealt with resolving the taxonomy of seaweeds and their phylogenetic relationships (e.g., Ragan et al 1994, De Clerck et al 2005, Gonz alez et al 2012, Leliaert et al 2012, Verbruggen et al 2016, Steen et al 2017. Moreover, researchers have studied the population genetics of seaweeds with a focus on genetic variability and its distribution within and among populations (e.g., Valero et al 2001, Mart ınez et al 2003, Guillemin et al 2008, Wang et al 2008, Andreakis et al 2009, Alberto et al 2010, Krueger-Hadfield et al 2011, Camus et al 2018) as well as their historical phylogeographic diversification (e.g., Tellier et al 2009, Buonomo et al 2017, Neiva et al 2018). Few studies have assessed different levels of genetic diversity in macroalgae.…”
mentioning
confidence: 99%